The Prevalence of HIV by Ethnic Group Is Correlated with HSV-2 and Syphilis Prevalence in Kenya, South Africa, the United Kingdom, and the United States - Kenyon, Chris Richard; Osbak, Kara; Buyze, Jozefien (Interdisciplinary Perspectives on Infectious Diseases, 2014)
Background. This paper investigates two issues: do ethnic/racial groups with high HIV prevalences also have higher prevalences of other STIs? and is HIV prevalence by ethnic group correlated with the prevalence of circumcision, concurrency, or having more than one partner in the preceding year? Methods. We used Spearman’s correlation to estimate the association between the prevalence of HIV per ethnic/racial group and HSV-2, syphilis, symptoms of an STI, having more than one partner in the past year, concurrency, and circumcision in Kenya, South Africa, the United Kingdom, and the United States. Results. We found that in each country HSV-2, syphilis, and symptomatic STIs were positively correlated with HIV prevalence (HSV-2: Kenya rho = 0.50, P = 0.207; South Africa rho-1, P = 0.000; USA rho-1, P = 0.000, Syphilis: Kenya rho = 0.33, P = 0.420; South Africa rho-1, P = 0.000; USA rho-1, P = 0.000, and STI symptoms: Kenya rho = 0.92, P = 0.001; South Africa rho-1, P = 0.000; UK rho = 0.87, P = 0.058; USA rho-1, P = 0.000). The prevalence of circumcision was only negatively associated with HIV prevalence in Kenya. Both having more than one partner in the previous year and concurrency were positively associated with HIV prevalence in all countries (concurrency: Kenya rho = 0.79, P = 0.036; South Africa rho-1, P = 0.000; UK 0.87, P = 0.058; USA rho-1, P = 0.000 and multiple partners: Kenya rho = 0.82, P = 0.023; South Africa rho-1, P = 0.000; UK rho = 0.87, P = 0.058; USA rho-1, P = 0.000). Not all associations were statistically significant. Conclusion. Further attention needs to be directed to what determines higher rates of partner change and concurrency in communities with high STI prevalence.